2020
DOI: 10.1186/s12866-020-01733-7
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of saliva microbiome in patients with oral lichen planus

Abstract: Background: Oral microbiota is not only important for maintaining oral health but also plays a role in various oral diseases. However, studies regarding microbiome changes in oral lichen planus (OLP) are very limited. To the best of our knowledge, there has been only two studies investigating salivary microbiome changes in OLP. Therefore, the purpose of this study was to identify the characteristic microbial profile in the saliva of OLP patients, with or without erosive lesions, and compare that with recurrent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 32 publications
8
37
1
Order By: Relevance
“…Recent studies have demonstrated that the oral microbiome composition in patients with OLP is different from that in normal control individuals [20][21][22]. Consistent with the ndings of previous studies, this study demonstrated that the salivary microbiome composition in patients with OLP was signi cantly different from that in normal control individuals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recent studies have demonstrated that the oral microbiome composition in patients with OLP is different from that in normal control individuals [20][21][22]. Consistent with the ndings of previous studies, this study demonstrated that the salivary microbiome composition in patients with OLP was signi cantly different from that in normal control individuals.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated that the oral microbiome composition in patients with OLP was different from that in normal control individuals [20][21][22]. This study demonstrated that the α diversity of oral microbiota in the OLP group was signi cantly higher than that in the NC group ( Fig.1A and B).…”
Section: Patients With Olp Exhibit Altered Oral Microbiome Compositionmentioning
confidence: 49%
“…The decreased Haemophilus and Neisseria and increased Actinomyces , Granulicatella , and Peptostreptococcus in the PC group and normalised abundances in the AA group demonstrated that aloe vera fermentation gel had benefits in the maintenance of microbial compositions [ 32 ]. Additionally, the decreased Haemophilus and Nesseria correlated the results of a previous study showing that decreased Proteobacteria, containing Haemophilus and Nesseria , is related to oral diseases such as gingivitis and cancer [ 33 36 ]. Actinomyces has long been recognised as a causative agent of actinomycosis as it increases the pathogenicity by attacking broken or necrotic tissues and is related to the incidence of RAS, with high abundance indicating poor prognosis for RAS [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 85%
“…different types of diseases [13][14][15][16] and changes during disease progression, 14,[17][18][19] suggesting that key causal pathogens may exist in various oral lesions. However, the role of the oral microbiota in inducing or progressing oral pathologies has not been thoroughly characterized.…”
mentioning
confidence: 99%